Responding to a school SARS-CoV-2 outbreak: Insights and policy implications emerging from the pandemic - Marrero, M. C.; Bonfini Petraccone, J.; Guida, S.; Montesi, A.; Fanti, A.; Gigliola, G.; Scalingi, S.; Aucone, R.; Russo, F. T.; Lovetro, D.; Facente, F.; Fermini, F.; et al. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The SARS-CoV-2 pandemic has affected also the school environment. Prolonged closures and the weakness of available data prevent a definitive answer to the question of school transmission. We report our experience of responding to COVID-19 cases in the school setting, presenting a case study of the management of an outbreak in a large school. Methods. The LHA/ASL Roma 1 has organized the School Units with a structure firmly rooted in the territory. At the local level, the District Unit mainly manages the relationship with schools, while the Hygiene and Public Health Service of the Prevention Department holds a coordinating and facilitating role. The HPHS carries out contact tracing activities facilitated by the schools, through the figure of the COVID-19 Contact Person, who is specifically trained to manage the preliminary stages of the reports.Results. Following several reports of COVID-19 suspect cases from two schools and, after a complex phase of contact tracing, it was possible to identify the major transmission chains. Furthermore, we performed a population-based screening on the entire school. Beyond the known transmission chains, for which quarantine was already in place, only five additional cases emerged, all asymptomatic, out of 1,231 swabs tested with RT-PCR.Conclusions. Our experience confirms that an active interaction between the school and the School Unit made it possible to quickly control a potentially dangerous outbreak. The large-scale screening test demonstrated the substantial absence of collateral transmission chains. Effective contact tracing allowed to set forth a successful response. Our model of intervention can be used to support public health protocols regarding school outbreaks.